Baden-Württemberg, Landesdenkmalpflege - Regierungsbezirk Stuttgart - Landesamt für Denkmalpflege (2008)
[Dt.:] Die Seite bietet ein übergreifendes Portal zur organisatorischen Struktur, zu Denkmalen, zu Projekten und Publikationen, darunter auch freie Elektronische Publikationen. - [Engl.:] This website gives a comprehensive subject gateway on the preservation and conservation of historical monuments in Baden-Wuerttemberg, Southwest Germany. There is information about its organisation, about monuments, projects and publications, including free online publications.